Determinación de la calidad del agua mediante medios químicos y biológicos de contaminación en el río Ambi, ciudad de Atuntaqui en la provincia de Imbabura - Carvajal Carabalí, Karen Geovanna (2022)
In this research, the water quality of the Ambi River was analyzed, since today there are several anthropogenic activities both in its surroundings and in the river itself, activities such as the exploitation of vegetation, the inappropriate use of chemicals in agriculture, among others. others. For this reason, the main objective of the research was to determine the water quality of the Ambi River located in the city of Atuntaqui, province of Imbabura through chemical and biological means for the analysis of contamination in it. Physical-chemical parameters such as BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), total dissolved solids, pH, turbidity, nitrates, phosphates and biological indicators were analyzed using the BMWP (Biological Monitoring Working Party) method. Among the main results of the investigation, it was found that, through physical-chemical analysis, the river water is not suitable for human consumption. In addition, a total of 13 orders and 21 families of macroinvertebrates were identified in the Ambi River. The score obtained for the BMWP index for the Ambi river was 37, which categorizes it in a Class III, with a quality not suitable for human consumption, with a yellow color, which means that the waters are contaminated. In this way, the main conclusion is that the water of the Ambi River has a poor quality, which is a product not only of the geomorphological conditions of the sector generated by natural processes, but mainly this contamination is caused by anthropogenic activities. such as the discharge of industrial and/or urban wastewater into the river without prior treatment, also altering the aquatic biota.